Protocol for Maintaining Alveolar Ridge Volume in Molar Immediate Implant Sites. Issue 4 (1st November 2017) - Johnson, Thomas M.; Berridge, Joshua P.; Baron, Dmitry
Abstract : Introduction: Numerous biomaterials are available for augmenting bone around dental implants. In contained extraction sockets, a demineralized freeze‐dried bone allograft (DFDBA) appears capable of maintaining dimensional stability of the alveolar ridge as well as mineralized alternatives but may yield a higher percentage of new vital bone. When DFDBA is used in large horizontal gap defects at molar immediate implant sites, graft containment and protection must occur through provisional restoration, an anatomic custom healing abutment, or by other means. Case Series: Two mandibular molar immediate implant sites received DFDBA covered by dense polytetrafluoroethylene membranes. Conclusion: The present report suggests a protocol for maintaining favorable dimensional stability of the alveolar ridge at molar immediate implant sites, while possibly minimizing residual peri‐implant biomaterial.